THE EFFECT OF DIFFERENT TYPES OF PACKAGING ON THE QUALITY OF SAGO NOODLES FORTIFIED WITH CATFISH PROTEIN CONCENTRATE (Pangasius hypophthalmus) DURING ROOM TEMPERATURE STORAGE - Sianturi, Desky Novita Sari; Buchari, Dewita; Suparmi, Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACT This study was purposed to determine the effect of different types of packaging on the quality of sago noodles fortified with catfish protein concentrate (Pangasius hypophthalmus) during room temperature storage. The method used was experimental method, with a Randomized Block Design (RBD) consisting of 3 different types of packing treatment is A1HDPE, A2Alumunium foil, and A3combination and as a group was the storage duration 0 day, 15 days, 30 days and 60 days.The series of research activities was divided into 3 stages, the first stage was preparation catfish protein concentrate, the second stage was making of sago noodles catfish protein concentrate, the third stage was packaging and storage of sago noodles catfish protein concentrate. Parameters measured include organoleptic test (appearance, aroma taste and texture), moisture content and Total Plate Count. The results showed of moisture content is A2(8,53-9,23%) and Total Plate Count (1,5 x 103- 2,2 x 103 cfu/g). In variance test with 95% confidence level for 60 days storage with different packaging showed significantly effect on organoleptic test (appearance, aroma, texture), moisture content and Total Plate Count. Keywords: sagoo noodle, packaging, stored, catfish protein concentrate Pangasius hypophthlalmus